ChemInform Abstract: Catalysis of Nickel Ferrite for Photocatalytic Water Oxidation Using [Ru(bpy)3]2+ and S2O82‐. Issue 13 (18th March 2013) - Hong, Dachao; Yamada, Yusuke; Nagatomi, Takaharu; Takai, Yoshizo; Fukuzumi, Shunichi
Abstract NiFe2O4 is an excellent catalyst for photocatalytic water oxidation with Na2S2O8 as a sacrificial oxidant and [Ru(bpy)3]2+ as a photosensitizer.